Evaluating Challenges and Competence for Employees in a Chain Providing Corrective Actions to Customers with Mobile Terminals - Mwegerano, Andi Mawazo (Archives of Business Research, 2014)
This article investigates challenges that are encountered by employees working in a chain handling customer issues in mobile phones. For a firm to get a competitive advantage over competitors, customer issues should be handled timely and efficiently. To achieve this goal, the employee working in the chain, among other things, must have adequate competence, education and the knowledge. This work attempts, through questionnaire survey, to analyse competences and challenges that are encountered by the employees working in the chain resolving the customer issues. Ordinal logistic regression and item analyse are used for the analyses in this article. The analyses results shows that there is a statistical difference of competences in difference service levels within the service chain. Clearly there is a managerial impact from the results of this work that all the levels in different stages must have a regular training of the products they are handling. Keywords: competence, customers, satisfaction, ordinal logistic regression, item analyses